USING THE CLUSTER METHOD FOR CONDUCTING LECTURES ON THEORETICAL MECHANICS - Mahmudov Zakirjon Sotivoldievich; K.S. Azamov (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
At the present stage of the country’s development, it is important for the teaching staff of higher educational institutions to train future specialists with modern pedagogical methods. The article considers the cluster method as applied to theoretical mechanics.